Evaluation of BCG's prophylactic effectiveness (Colombia Medica, 1990)
Discussion on the BCG protective effect has not yet ended. However, recent studies have been carried out in tropical countries, and the present research shows consistent evidence that the BCG has a protective effect against the pulmonary form of the disease (53.0%, 62.5%, and 71.0%, respectively). Thus, vaccination programs for newborn babies in these countries should continue until follow-up studies provide new evidence. At the same time, it is necessary to develop sensitive new methods of diagnosis for infantile tuberculosis.